Post-poliomyelitis syndrome: case report Síndrome pós-polio: relato de caso - Marco Antonio Orsini Neves; Mariana Pimentel de Mello; Viviane Vieira dos Santos; Osvaldo J. M. Nascimento; Reny de Souza Antonioli; Gabriel Rodrigues de Freitas; Marcos R.G. de Freitas (Arquivos de Neuro-Psiquiatria, 2007)
The post-polio syndrome (PPS) is an entity characterized for an episode of muscular weakness and/or abnormal muscular fatigue in individuals that had presented acute polio years before. We report the case of PPS in a patient, 40 years, that thirty-five years after had had paralytic poliomyelitis, developed new symptoms of fatigue, muscular atrophy, dyspnea, difficulties in deambulation and muscular and joint pain. The electromyographic findings revealed injuried neurons of the anterior horn of the marrow and reinnervation after muscular tests. A síndrome pós-polio (SPP) é entidade caracterizada por um episódio de fraqueza muscular e/ou fadiga muscular anormal em indivíduos que apresentaram poliomielite aguda anos antes. Relatamos o caso de SPP em um paciente, 40 anos, que trinta e cinco anos após haver tido poliomielite paralítica, desenvolveu novos sintomas de fadiga, atrofia muscular, dispnéia, dificuldades na deambulação e dores articulares e musculares. Os achados eletromiográficos revelaram acometimento dos neurônios da ponta anterior da medula e reinervação após a realização de testes musculares.